Meritocracy or reputation? The role of rankings in the sorting of international students across universities - Yasemin Nuhoḡlu Soysal; Roxana D. Baltaru; Héctor Cebolla-Boado (Globalisation, Societies and Education, 2022)
University rankings have gained prominence in tandem with the global race towards excellence and as part of the growing expectation of rational, scientific evaluation of performance across a range of institutional sectors and human activity. While their omnipresence is acknowledged, empirically we know less about whether and how rankings matter in higher education outcomes. Do university rankings, predicated on universalistic standards and shared metrics of quality, function meritocratically to level the impact of long-established reputations? We address this question by analysing the extent to which changes in the position of UK universities in ranking tables, beyond existing reputations, impact on their strategic goal of international student recruitment. We draw upon an ad hoc dataset merging aggregate (university) level indicators of ranking performance and reputation with indicators of other institutional characteristics and international student numbers. Our findings show that recruitment of international students is primarily determined by university reputation, socially mediated and sedimented over the long term, rather than universities' yearly updated ranking positions. We conclude that while there is insufficient evidence that improving rankings changes universities' international recruitment outcomes, they are nevertheless consequential for universities and students as strategic actors investing in rankings as purpose and identity.
Keywords: 300; university rankings; reputational prestige; quantification and metrics; UK higher education; international student recruitment; institutional level analysis